2010
DOI: 10.11157/anzswj-vol22iss2id207
|View full text |Cite
|
Sign up to set email alerts
|

Parenting adopted children and supporting adoptive parents: Messages from research

Abstract: This article considers adoption from the perspective of parents, especially the strategies that they employ to enhance attachments and build positive parent-child relationships. The article draws particularly on recent New Zealand research regarding intercountry adoptive parenting, as well as overseas literature on good adoptive parenting practice generally in domestic and intercountry adoption. It also considers the research on methods of supporting parents who adopt and whether there are gaps in legislation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Research into the experiences of adoptive parents suggest they often face unique challenges that can influence their mental health and parenting capacity (Barnett et al, 2019; Brodzinsky & Schechter, 1990; Gibbs, 2010). Abidin (1990) suggested that when parents' sense of well‐being is threatened, their capacity to parent is diminished.…”
Section: Background Literature On Adoptive Parenthoodmentioning
confidence: 99%
“…Research into the experiences of adoptive parents suggest they often face unique challenges that can influence their mental health and parenting capacity (Barnett et al, 2019; Brodzinsky & Schechter, 1990; Gibbs, 2010). Abidin (1990) suggested that when parents' sense of well‐being is threatened, their capacity to parent is diminished.…”
Section: Background Literature On Adoptive Parenthoodmentioning
confidence: 99%
“…Since these legal and policy initiatives, the needs of adoptive parents, methods of adoption support and the effectiveness of services have received greater attention in England, but also elsewhere (see for example, Argent 2003;Bonin et al 2013;Holmes et al 2013;Lewis and Ghate 2015;McKay and Ross 2011;Monck and Rushton 2009;Rushton and Dance 2002;Rushton et al 2006;Rushton and Monck 2009;Selwyn et al 2014;Stock et al 2016 andThomas 2013). This interest is evident in the case of inter-country adoption also (see Gibbs 2010). Whilst services might be delivered to birth families, those made available to adoptive families signify the intention to encourage the best possible outcomes, aiding stability for the adoptive child by guarding against placement disruption.…”
Section: Background To the Provision Of Adoption Supportmentioning
confidence: 99%